Measuring party positions in Europe: The Chapel Hill expert survey trend file, 1999–2010. (January 2015) - Bakker, Ryan; de Vries, Catherine; Edwards, Erica; Hooghe, Liesbet; Jolly, Seth; Marks, Gary; Polk, Jonathan; Rovny, Jan; Steenbergen, Marco; Vachudova, Milada Anna
This article reports on the 2010 Chapel Hill expert surveys (CHES) and introduces the CHES trend file, which contains measures of national party positioning on European integration, ideology and several European Union (EU) and non-EU policies for 1999−2010. We examine the reliability of expert judgments and cross-validate the 2010 CHES data with data from the Comparative Manifesto Project and the 2009 European Elections Studies survey, and explore basic trends on party positioning since 1999. The dataset is available at the CHES website.